REVITALISASI PENDIDIKAN DASAR BERBASIS NILAI ISLAM: MEWUJUDKAN GENERASI CERDAS DAN BERAKHLAK - Idhar, Idhar (Prodi PGMI STIT Sunan Giri Bima, 2024)
This study examines the revitalization of elementary education based on Islamic values to shape intelligent and virtuous generations. Elementary education plays a fundamental role in building the foundation of knowledge, skills, and values that will influence individuals' lives in the future. In this context, the integration of educational sciences and Islamic values emerges as a potential approach to create a holistic educational system that combines intellectual intelligence with the development of noble character. This research employs a literature review method by analyzing various studies related to the application of Islamic values in elementary education. The findings indicate that such integration can strengthen students' spiritual character, enhance curriculum relevance, and prepare a generation ready to face global challenges without losing their moral identity. Islamic values such as tauhid (monotheism), tawadhu’ (humility), and social justice are implemented in the educational process to cultivate individuals who excel not only academically but also possess social commitment and personal integrity. The study also identifies challenges in implementing this integration, such as cultural resistance and resource limitations, which require collaboration among stakeholders. This research recommends the inclusive application of a curriculum based on Islamic values to ensure relevant and sustainable education in shaping a future generation that excels both intellectually and morally.